2014
DOI: 10.1177/0956797614528522
|View full text |Cite
|
Sign up to set email alerts
|

When Cognitive Control Is Not Adaptive

Abstract: In order to engage in goal-directed behavior, cognitive agents have to control the processing of task-relevant features in their environments. Although cognitive control is critical for performance in unpredictable task environments, it is currently unknown how it affects performance in highly structured and predictable environments. In the present study, we showed that, counterintuitively, top-down control can impair and interfere with the otherwise automatic integration of statistical information in a predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(60 citation statements)
references
References 17 publications
6
53
1
Order By: Relevance
“…Both modes have value in the appropriate contexts (Block & Block, 1980; Bocanegra & Hommel, 2014; Otto, Gershman, Markman, & Daw, 2013). For example, model-free functioning is more adaptive than is model-based functioning in environments that are unpredictable (e.g., Tops, Boksem, Luu, & Tucker, 2010), and where the future availability of resources is unknown (e.g., Del Giudice, 2014).…”
Section: How Might the P Factor Reflect Meaningful Functional Variation?mentioning
confidence: 99%
“…Both modes have value in the appropriate contexts (Block & Block, 1980; Bocanegra & Hommel, 2014; Otto, Gershman, Markman, & Daw, 2013). For example, model-free functioning is more adaptive than is model-based functioning in environments that are unpredictable (e.g., Tops, Boksem, Luu, & Tucker, 2010), and where the future availability of resources is unknown (e.g., Del Giudice, 2014).…”
Section: How Might the P Factor Reflect Meaningful Functional Variation?mentioning
confidence: 99%
“…In most experimental paradigms, cognitive control is adaptive because subjects have to overcome the automatic activation of an incorrect response triggered by an irrelevant feature which is similar or identical to those that need to be attended [Botvinick et al, 2001]. In this context, Bocanegra and Hommel [2014] showed that a predictive feature (an implicit S-R contingency that the study participants were unaware of), which was clearly task-irrelevant but would nevertheless improve performance if (automatically) taken into account, improved task performance only when participants performed the task rather automatically (i.e., with little cognitive control requirements) but not when they had been required to exert high levels of cognitive control (which actually had a detrimental effect on performance). In this context, Bocanegra and Hommel [2014] showed that a predictive feature (an implicit S-R contingency that the study participants were unaware of), which was clearly task-irrelevant but would nevertheless improve performance if (automatically) taken into account, improved task performance only when participants performed the task rather automatically (i.e., with little cognitive control requirements) but not when they had been required to exert high levels of cognitive control (which actually had a detrimental effect on performance).…”
Section: Introductionmentioning
confidence: 99%
“…A conjecture guides the perceptual search process by acting as a task set (e.g. see Bocanegra & Hommel, 2014;Schneider & Shiffrin, 1977;Wolfe, 2012). When a search attempt succeeds at finding a matching phenomenal experience, this is called a confirmation event.…”
Section: The M-mode Of Phenomenal Explorationmentioning
confidence: 99%
“…An anomaly initiates the memory search process by acting as a retrieval cue (e.g. see Bocanegra & Hommel, 2014;Davelaar & Raaijmakers, 2012;Sternberg, 1969). When a search attempt fails to retrieve a matching conceptual interpretation, this is called a falsification event.…”
Section: The D-mode Of Conceptual Ruminationmentioning
confidence: 99%